Liver fibrosis among infants with t(1;22)(p13;q13) acute megakaryoblastic leukemia: a case report and literature review - Arad-Cohen, Nira; Attias, Ori; Zohar, Yaniv; Messinger, Yoav H. (Frontiers in Oncology, 2024)
This case report describes a 2-month-old girl with acute megakaryoblastic leukemia (AMKL) harboring the t(1;22)(p13;q13) translocation, resulting in the RBM15::MRTFA fusion gene. She presented with massive hepatosplenomegaly and liver fibrosis and achieved complete remission with chemotherapy; the liver fibrosis resolved within 2.5 months. After 12 years of follow-up, the patient remained in good health, without relapse. Reviewing the literature on eight additional similar cases of liver fibrosis, this subtype of AMKL predominantly affects females below 3 months of age, with a median onset at 6 weeks. High rates of severe complications were observed, with five of nine patients dying within 10 weeks of diagnosis. The authors hypothesized that the proliferation of abnormal megakaryoblasts within the liver leads to the release of profibrotic cytokines, such as TGF-β1, which induces liver fibrosis similar to that observed in transient abnormal myelopoiesis in Down syndrome. Careful monitoring of liver function and reduced-intensity chemotherapy are recommended for this very young patient population. Nonetheless, long-term survival can be achieved with aggressive supportive care and treatment.